2019
DOI: 10.1101/801738
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High and stable ATP levels prevent aberrant intracellular protein aggregation

Abstract: 23ATP is the main source of chemical energy in all life and is maintained at several millimolar 24 in eukaryotic cells. However, the mechanisms responsible for and physiological relevance of 25 this high and stable concentration of ATP remain unclear. We herein demonstrate that 26 AMP-activated protein kinase (AMPK) and adenylate kinase (ADK) cooperate to maintain 27 cellular ATP levels regardless of glucose concentrations. Single cell imaging of ATP-reduced 28 yeast mutants revealed that ATP concentrations in… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 63 publications
(93 reference statements)
0
2
0
Order By: Relevance
“…Particularly, AMP signaling to AMP-activated protein kinase (AMPK) plays a critical role in adjusting ATP-producing and ATP-consuming processes (90, 94) (Figure 1). In several cancers, it has been demonstrated that AMPK, a master regulator of cellular energy homeostasis, possesses tumor suppressor function (95)(96)(97) (98). On the other end, AMP-deaminase (AMPD) and 5 ′ -nucleotidase (5 ′ -NT) suppress AMPK via decreasing AMP cellular levels (22,99,100).…”
Section: Adenylate Kinase-mediated Amp Metabolic Signaling In Cancer mentioning
confidence: 99%
“…Particularly, AMP signaling to AMP-activated protein kinase (AMPK) plays a critical role in adjusting ATP-producing and ATP-consuming processes (90, 94) (Figure 1). In several cancers, it has been demonstrated that AMPK, a master regulator of cellular energy homeostasis, possesses tumor suppressor function (95)(96)(97) (98). On the other end, AMP-deaminase (AMPD) and 5 ′ -nucleotidase (5 ′ -NT) suppress AMPK via decreasing AMP cellular levels (22,99,100).…”
Section: Adenylate Kinase-mediated Amp Metabolic Signaling In Cancer mentioning
confidence: 99%
“…Voltage-dependent anion channels (VDACs) located in the mitochondrial outer membrane (MOM) [ 41 ] and adenine nucleotide translocators (ANTs) on the inner mitochondrial membranes (IMM) [ 42 , 43 ] facilitate the export of ATP into cytosol where ATP accumulation has been observed to be the highest [ 44 ]. The high physiological concentration of ATP in cytoplasm may be used to control the pathological aggregation of macromolecules that coacervate as a result of transient interactions during LLPS in the cytoplasm and nucleus [ 45 , 46 ]. A major hallmark of ALS/FTD is the presence of FUS inclusion in the cytoplasm.…”
Section: Atp Regulates Biomolecular Condensatesmentioning
confidence: 99%